Sex Work and the Indian Judiciary: Shifting Narratives on Consent and Choice - Ms Riya Kanwar (Journal of Informatics Education and Research, 2025)
Sex work in India occupies a paradoxical legal and social position—while the act of sex work is not criminalized per se, surrounding activities are penalized under the Immoral Traffic (Prevention) Act, 1956 (ITPA), leading to systemic marginalization, police harassment, and social stigma. This paper critically examines the evolving stance of the Indian judiciary, tracing the shift from a paternalistic, moralistic framework towards a rights-based, autonomy-respecting interpretation of sex workers' legal status. Landmark judgments such as State of Maharashtra v. Madhukar Narayan Mardikar and the Budhadev Karmaskar case series demonstrate an important judicial acknowledgment of sex workers’ dignity, agency, and right to livelihood under Articles 14, 19, and 21 of the Constitution. The paper further explores how this judicial evolution aligns with feminist and intersectional perspectives that emphasize consent, choice, and the compounded oppression faced by sex workers due to caste, poverty, and gender. It highlights the urgent need to reform outdated legislation like the ITPA, advocating for decriminalization and integration of sex workers into the legal and policy mainstream. Drawing from recent Supreme Court directives, NGO reports, and international models, the study recommends a shift from criminalization to empowerment, ensuring sex workers are treated not as victims or criminals but as citizens entitled to constitutional protections. The conclusion calls for comprehensive legislative reform, institutional sensitization, and inclusion of sex workers in policy formulation to realize a just and equitable future.